Remote Sensing of Biomass in the Miombo Woodlands of Southern Africa: Opportunities and Limitations for Research - Ribeiro, Natasha; Cumbana, Micas; Mamugy, Faruk; Chaúque, Aniceto (IntechOpen, 2012)
None